2005
DOI: 10.1002/jmv.20503
|View full text |Cite
|
Sign up to set email alerts
|

Genotype, phylogenetic analysis, and transmission pattern of occult hepatitis B virus (HBV) infection in families of asymptomatic HBsAg carriers

Abstract: Occult hepatitis B is defined by the presence of hepatitis B virus (HBV) DNA in the serum in absence of hepatitis B surface antigen (HBsAg). Studies were conducted to screen for occult HBV infection among family members of HBV carriers, incidentally detected positive for HBV infection with a view to assess the pattern of virus transmission among them. Nested PCR assay, employing independent sets of primers to surface and core genes, was used for detection of HBV DNA in serum samples from 28 index cases with as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 27 publications
6
49
1
Order By: Relevance
“…To avoid false-positive results, instructions to prevent cross-contaminations were strictly followed and the results were considered valid only when they were consistently obtained in duplicate [20] .…”
Section: Mutations In the Bcp And Pc Regions Of Hbvmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid false-positive results, instructions to prevent cross-contaminations were strictly followed and the results were considered valid only when they were consistently obtained in duplicate [20] .…”
Section: Mutations In the Bcp And Pc Regions Of Hbvmentioning
confidence: 99%
“…The HBV genotype was determined using the restriction fragment length polymorphism (RFLP) method as described by Lindh et al [19] and some of them especially those who belonged to genotype A were directly sequenced for the detection of subgenotypes (A1 or A2) as described previously [20] .…”
Section: Genotyping Of Hbvmentioning
confidence: 99%
“…Occult HBV infection was detected even among family members of HBV carriers. 5 This so-called occult HBV infection has been identified by sensitive polymerase chain reaction (PCR) assays that detect low levels of HBV DNA in serum and/or liver tissue of HBsAg-negative subjects. [6][7][8] Since the early 1980s, several studies have reported the detection of HBV DNA in both tumorous and non-tumorous liver tissue of HBsAg-negative HCC patients.…”
mentioning
confidence: 99%
“…Interestingly, this was not invariant, as sample M31 (gC, sG145R), which also carried sI195T, did not influence the expression of the D2H5 epitope. Whilst sG145R has been reported to cause testing failures in genotype C (Datta et al, 2006;Hou et al, 2001), the addition of the concurrent sI195T, a distant codon change towards the C terminus, in sample M31 (gC) seems to have acted to preserve the HBsAg antigenicity despite a sG145R substitution. Sloan et al (2008) Major disruption of the a determinant was only seen rarely.…”
mentioning
confidence: 99%